Changes in UK parental mental health symptoms over 10 months of the COVID-19 pandemic - Skripkauskaite, S; Creswell, C; Shum, A; Pearcey, S; Lawrence, P; Dodd, H; Waite, P (Wiley, 2023)
Background The threats to health, associated restrictions and economic consequences of the COVID-19 pandemic have been linked to increases in mental health difficulties for many. Parents, in particular, have experienced many challenges such as having to combine work with home-schooling their children and other caring responsibilities. Yet, it remains unclear how parental mental health has changed throughout the pandemic or what factors may have mitigated or compounded the impact of the pandemic on parents' mental health.